Panel 7 – Pathogenesis of otitis media – a review of the literature between 2015 and 2019. (March 2020) - Thornton, R.B.; Hakansson, A.; Hood, D.W.; Nokso-Koivisto, J.; Preciado, D.; Riesbeck, K.; Richmond, P.C.; Su, Y.C.; Swords, W.E.; Brockman, K.L.
Abstract: Objective: To perform a comprehensive review of the literature from July 2015 to June 2019 on the pathogenesis of otitis media. Bacteria, viruses and the role of the microbiome as well as the host response are discussed. Directions for future research are also suggested. Data sources: PubMed database of the National Library of Medicine. Review methods: PubMed was searched for any papers pertaining to OM pathogenesis between July 2015 and June 2019. If in English, abstracts were assessed individually for their relevance and included in the report. Members of the panel drafted the report based on these searches and on new data presented at the 20th International Symposium on Recent Advances in Otitis Media. Conclusions: The main themes that arose in OM pathogenesis were around the need for symptomatic viral infections to develop disease. Different populations potentially having different mechanisms of pathogenesis. Novel bacterial otopathogens are emerging and need to be monitored. Animal models need to continue to be developed and used to understand disease pathogenesis. Implications for Practice: The findings in the pathogenesis panel have several implications for both research and clinical practice. The most urgent areas appear to be to continue monitoring the emergence of novel otopathogens, and the need to develop prevention and preventative therapies that do not rely on antibiotics and protect against the development of the initial OM episode.